How can we further rights-based and evidence-based policies on migrant and ethnic minority health?. (July 2019) - Ingleby, David; Smith, Alyna; Severoni, Santino
Abstract: There is an urgent need to draw the attention of politicians and the public to the health inequities facing migrants and ethnic minorities to foster health policy reforms based on human rights and sound evidence. Today, it is more important than ever for researchers and organisations promoting migrant health to join forces and intensify their efforts to get policies improved. A workshop was held to consider how this should be done. Three speakers put forward in turn perspectives based mainly on human rights, scientific evidence and a combination of both. Highlights: Researchers and advocates need to join forces to confront the challenge of antimigrant sentiment and 'fact-free politics'. More attention must be paid to effective communication with the public and policymakers. Better policies must be based on both human rights and sound evidence.